2D Metal‐Organic Framework Materials for Membrane‐Based Separation. Issue 1 (28th November 2019) - Peng, Yuan; Yang, Weishen
Abstract: Metal‐organic framework (MOF) nanosheets are promising membrane building blocks for ultimate and efficient separation because of the diversified structures, ultrathin thickness, and tunable chemical functionalities. Targeting at membrane‐based separation, representative developments of top‐down and bottom‐up methods to produce high‐quality MOF nanosheets are introduced, and the merits and demerits of each method are carefully elucidated. A summary of fabrication approaches of MOF nanosheet‐based membranes is also put forward to establish a comprehension on the relationship between membrane structure and the eventual separation performance. Moreover, classical characterization techniques to get an insight into these 2D materials are addressed. Last but not least, concerns on the challenges and opportunities for these novel membranes are demonstrated in order to provide some guidelines for the development in the future. Abstract : Metal‐organic framework (MOF) nanosheets have great potential to serve as state‐of‐the‐art building units of membranes for precise and ultimate separation. This review provides a comprehensive summary of the separation application‐oriented progresses of MOF nanosheets. The top‐down and bottom‐up fabrication of disintegrated MOF nanosheets, nanosheet assembly into selective membranes, characterizations, and preliminary separation–performance relationship are presented.